Penataan Kampung Nelayan Tambakrejo Pada Lahan Bekas Sungai di Kota Semarang - Bagus Irawan; Rosita Herawati (Badan Riset dan Inovasi Daerah Kota Semarang, 2026)
The redevelopment of Tambakrejo Fishermen Settlement in Semarang City was part of the East Flood Canal normalization program, which required the relocation of 97 fishermen households from riverbank areas to a new settlement developed on the former Kali Banger riverbed. This study aims to analyze the integration of geotechnical engineering, adaptive waterfront settlement, and collaborative governance in the development of a sustainable coastal relocation area. A mixed-method case study approach was employed through the analysis of technical documents, engineering reports, planning records, and policy-related documents.The results indicate that the relocation site was characterized by soft soil and active mud deposits with an estimated natural consolidation period of 67.225 years and a settlement rate of 5.74 cm/year, exceeding the allowable limit for residential infrastructure. A hybrid reinforcement system consisting of Polyfelt PEC-50 geotextile and bamboo piles successfully reduced incremental settlement to 0.4–0.5 cm/year and increased the safety factor to 1.47–1.48, exceeding the minimum design requirement of 1.4. The redevelopment concept integrated fishermen housing, green open spaces, drainage systems, boat docking facilities, and public infrastructure to support environmental quality and livelihood sustainability.This study proposes an integrated model of sustainable coastal relocation that combines adaptive geotechnical engineering, waterfront settlement planning, collaborative governance, and livelihood sustainability. The findings demonstrate that successful coastal relocation requires not only technical feasibility but also social acceptance and institutional collaboration to achieve safe, adaptive, and sustainable coastal settlements.